(untitled) (Research, Society and Development, 2023)
Basic sanitation has faced few advances over the decades. Currently, concern about environmental issues, especially the management of water resources, is evident. This ranges from the adequate supply of water in terms of quality and quantity to meet the needs of the population to the correct treatment and disposal of waste resulting from the use of this resource. In this context, this study aims to analyze the feasibility of alternative and low-cost technologies for effluent treatment, focusing on the Biological Sewage Treatment Station (BIOETE), in order to resolve the Brazilian deficit in this requirement. From this perspective, the object of this study will be the innovative methodology used by the sanitation company Biosan in Minas Gerais. This approach has emerged as a vital option in economic and sustainable matters for Brazilian municipalities. The analysis will be based on a robust methodology, which includes bibliographic review and data collection, using sources such as Google Scholar, ScienciDirect, Capes Periodicals, Revista Brasileira de Ciências Ambientais, as well as banks of theses and dissertations from renowned institutions such as USP, UFPE and UTFPR. Therefore, the results obtained demonstrated that BIOETE not only brings benefits to health and the environment, but also stands out for its low implementation cost and lack of energy consumption. Consolidating its economic viability and environmental sustainability as a solution for the treatment of domestic and industrial effluents. The in-depth analysis carried out highlights its effectiveness, contributing significantly to overcoming the existing deficit in Brazilian basic sanitation.